SISTEM INFORMASI PENERIMAAN SISWA BARU ACHMADDIN BERBASIS WEBSITE - Riswan, Riswan; -, Nilawati (JURNAL AKADEMIKA, 2023)
In the data processing process using handwriting, so there are still many obstacles in data processing, such as the difficulty of recording registration data, planning previously planned activities because the data search process is slow, the data does not appear automatically so you have to write Jambi absence of a database. The purpose of this study is to analyze the current system, in order to overcome the problems encountered in the Achmaddin Kindergarten Early Childhood Unit in Jambi City, by designing a Web-Based Information System for Admission of New Student Participants at the Achmaddin Early Childhood Unit in Jambi City. Research Framework The stages that will be carried out in solving the problems discussed are identifying, searching for information based on theoretical foundations, collecting data using observation Achmaddin Early Childhood Unit in Jambi City. The system development method uses a waterfall model, the implementation of this research uses the PHP programming language and MySQL DBMS, to produce data processing applications that are expected to facilitate data processing and report generation.